Diseño y elaboración de bloques de hormigón prototipo utilizando partículas de caucho. - Lara Guerrero, Edison Javier (2018)
The problem in the disposal of rubber particles, creates a necessity to propose new alternatives to approach the mitigation of the environmental impact generated by the contamination of vehicular tires. In this sense, taking advantage of this recycled material is proposed for use in construction materials. This investigation consists in the design and elaboration of a prototype concrete block using rubber particles, for different percentages of substitutions by fine aggregate that has similar technical and economic characteristics of a conventional type B concrete block, complying with the NTE INEN 3066 2016-11 norm. The proposal, is the replacement of percentages (10%, 15% and 20%) in volume of fine aggregates by rubber particles product of the crushing of tire. The results show that the alternative is viable under the parameters mentioned above; therefore, the concrete block with 20% rubber particles showed a minimum net compression strength of 3,69 MPa. complying with the established. The price of the prototype concrete block with 20% rubber particles is cheaper than a conventional block type B proposed in this research.